Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4049/jimmunol.178.4.2132
|View full text |Cite
|
Sign up to set email alerts
|

High IFN-γ Production of Individual CD8 T Lymphocytes Is Controlled by CD152 (CTLA-4)

Abstract: CD8 T cell expansion and cytokine production is needed to generate an effective defense against viral invasion of the host. These features of CD8 T lymphocytes are regulated, especially during primary responses, by positive and negative costimulation. We show in this study that surface expression of CD152 is highly up-regulated on activated CD8 T lymphocytes during primary immune responses, suggesting a prominent regulatory role. Indeed, production of the proinflammatory cytokine IFN-γ, but not TNF-α, by CD8 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Since recently, the traditional view of CTLA-4 inhibitory effects on T cell responses was merely attributed to its inhibitory effect of inducing cell cycle arrest (12,34,53). New data now demonstrate that CTLA-4 signaling can indeed down-regulate effector molecules such as IFN-␥ of individual CD8 T cells (35). One or both functions of CTLA-4 mentioned could explain the enhanced Ab production caused by the genetic inactivation of CTLA-4 on B cells (12,34,54,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since recently, the traditional view of CTLA-4 inhibitory effects on T cell responses was merely attributed to its inhibitory effect of inducing cell cycle arrest (12,34,53). New data now demonstrate that CTLA-4 signaling can indeed down-regulate effector molecules such as IFN-␥ of individual CD8 T cells (35). One or both functions of CTLA-4 mentioned could explain the enhanced Ab production caused by the genetic inactivation of CTLA-4 on B cells (12,34,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Surface and intracellular expression of CTLA-4 was detected using immunofluorescent liposomes as described elsewhere (35). Cytometric analyses were performed using a FACSCalibur (BD Biosciences) and CellQuest software (BD Biosciences).…”
Section: Facs Analysismentioning
confidence: 99%
“…Initially, downstream targets of the Tc1 lineage were analyzed to confirm the Tc1 conversion, as it is well established that inhibiting CTLA-4 enhances Tc1 differentiation. 29,35 First, flow cytometric analysis showed that the CTLA-4-crosslinked cells more effectively retained their Tc17 profile, even under Tc1-skewing conditions, compared with the activated control cells (Fig. 5A).…”
Section: Ctla-4-mediated Effects On Stats Stabilize Tc17 Differentiationmentioning
confidence: 99%
“…33,34 Focusing on the major effector cells that eliminate tumors, CTLA-4-deficient CD8 C T cells exhibited increased production of IFNg and granzyme B. 29,35 In a Tc17 milieu, CTLA-4 supports Tc17 differentiation and limits the lineage plasticity of the Tc17 phenotype by inhibiting the expression of central factors of the Tc1 program, namely, IFNg and granzyme B. 36 This indicates that CTLA-4 affects the Tc1 and Tc17 lineage programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation